Inkarnacje tożsamości młodzieży w przestrzeni mediów społecznościowych - Górecka, Jagoda (Kultura-Społeczeństwo-Edukacja, 2023)
Adolescence is a period of transition between the child identity to more complex and coherent structure of oneself. A mature identity is shaped throughout the entire life and refers to the broader context of reality. The contemporary youth research orientations indicate the psychological, social and cultural dimensions as an inextricably interconnected. The article presents a contemporary concepts of youth identity in the reality of social media. The aim is to consider the significance of social media platforms for creating self-identifications and personal images. In the era of digital communication and visual culture, the role of autocreation has become an explicit component of manifesting ones identity. In the postmodern concepts of identities the social construction and subjective creation has been indicated as well as emerging ideology of consumerism. Although, the contemporary youth studies put the focus on digital media and new technologies, there is a growing need of deeper insights of the dynamic changes of personality and teenage identities in relation to social media sites.